Happiness and victimization in Latin America (2016)
In recent decades, studies on economics have identified happiness as a life quality indicator that not only accounts for individuals’ socioeconomic improvement but also accounts for their interactions with institutions and public goods, such as personal safety and protection of life. This study examines the determinants of individual happiness of Latin American citizens by focusing on whether the individual had been a victim of a crime in the last twelve months. To do this, a generalized ordered logit with partial constraints is used to analyze data obtained from the Americas Barometer Survey of 2014. The individual self- reported level of life satisfaction is used to study its relationship with having been a victim of a crime during the previous year. The results suggest the existence of a negative relationship between having been a victim of a crime in the past twelve months and being very satisfied with life.